Selenium induced lower respiratory potential in Glycine max (L.) Merr. - Špela MECHORA; Mateja GERM (Acta Agriculturae Slovenica)
Effect of selenium (Se) was studied in soybean (Glycine max (L.) Merr.) cv. Olna in Ljubljana, Slovenia. Se was added to plants as foliary spraying. Quantum yield of photosystem II (PSII) and respiratory potential measured as ETS activity of mitochondria were measured two times in the growing season. Respiratory potential was higher in young plants compared to mature plants. Se induced the lowering of respiratory potential. Addition of Se had no effect on quantum yield of photosystem II.